Long-acting new generation antipsychotics in the maintenance treatment of bipolar disorders - E. Yavuz; K. Altınbaş (European Psychiatry, 2022)
Introduction Maintaining remission, preventing from future episodes, better treatment adherence and improving the quality of life are main aims of long-term treatment in bipolar disorders (BD). In recent years, new generation long-acting injectable (LAI) antipsychotics have been frequently used in maintenance treatment for bipolar disorders.